The progress of assessment methods and treatments of neovascular glaucoma secondary to central retinal vein occlusion - Qu, Sheng; Zou, Ying; Yang, Li; Wu, Hong (Frontiers in Medicine, 2024)
Neovascular glaucoma is a condition that results from central retinal vein occlusion and often leads to blindness. Accurate evaluation and appropriate treatment are crucial for patients. However, there is currently no uniform and clear standard to differentiate between ischemic and non-ischemic central retinal vein occlusion. Also, the assessment of neovascular glaucoma progression is uncertain. Meanwhile, although pan-retinal photocoagulation is a standard treatment to prevent the onset of neovascular glaucoma, its actual efficacy and the timing of intervention remain highly controversial. It is still challenging to balance the risks of side effects in the visual field against the uncertain effectiveness of the treatment. This paper delves into the pathogenesis of neovascular glaucoma to understand the development of therapeutic approaches. By taking into account various assessment criteria of central retinal vein occlusion and neovascular glaucoma over the years, combining functional tests and morphological tests provides the most accurate and rigorous solution. The age of patients, the extent, location, and duration of retinal ischemia are the primary factors that affect the severity and extent of ischemic central retinal vein occlusion and induce serious complications. From the perspective of prevention and treatment, the ischemic index is closely related to the development of neovascularization. The paper provides essential insights into the mechanism, efficacy, complications, and optimal timing of pan-retinal photocoagulation. Comparing the treatment effects of pan-retinal photocoagulation and intravitreal anti-VEGF injections, we suggest a combination of both treatments to explore effective treatment with fewer side effects in the long term. This article details the debate on the above issues and explores ideas for the clinical diagnosis and preventive treatment of neovascular glaucoma that results from ischemic central retinal vein occlusion.